Peningkatan Kemampuan Evaluasi Guru Melalui Supervisi Klinis di Sekolah Binaan SD Negeri 11/III Simpang Empat Semester Ganjil Tahun Ajaran 2022/2023 - Mat Sujarti (Departement of Mathematics Education, 2023)
This study aims to obtain data/information and discuss how to Improve Teacher Evaluation Capacity Through Clinical Supervision in Target Schools of SD Negeri 11/III Simpang Empat Odd Semesters for the 2022/2023 Academic Year. This type of research is School Action Research (PTS). This research was conducted at SD Negeri 11/III Simpang Empat which is located at Simpang Empat, Danau Kerinci District, Kerinci Regency, Jambi Province. SD Negeri 11/III Simpang Empat is one of the schools that the author assisted in the academic year in Kerinci Regency. This research was conducted in the odd semester of the 2022/2023 school year, starting from August to September 2022. The subjects in this study were 6 teachers at SD Negeri 11/III Simpang Empat. The research procedure consisted of two cycles with four research stages starting from planning, implementing, observing and reflecting. Data collection techniques in this study used observation and documentation sheets. The collected data were analyzed using the percentage formula. The results of the study showed that there was an increase in the teacher's evaluation ability through clinical supervision at SD Negeri 11/III Simpang Empat Odd Semester Schools for the 2022/2023 Academic Year starting from the pre-cycle, cycle I and cycle II.